Policy Analysis: Parental Rights on Vaccination - Right to be Educated - Devi, Ashna; Gosai, Sharnit (Tecno Scientifica Publisher, 2023)
This paper examined evidence from various perspectives on the vaccination debate in the United States. It discusses reasons that revolve around the concept of parental rights regarding vaccination, while also exploring numerous factors that influence shifting opinions on this controversy. The experiences of individuals are taken into consideration, alongside the broader population. Historical events that contribute to the discussion of vaccine hesitancy are presented as evidence. The paper delves into the impact of misinformation and its ability to influence the general public through various media outlets. The contribution of physicians in educating their patients about childhood vaccination is also considered. Additionally, the paper explores the balance between maintaining human rights to religious practice and ensuring maximum protection against contagious diseases in our communities.